CD147 is tightly associated with lactate transporters MCT1 and MCT4 and facilitates their cell surface expression. - Kirk, P; Wilson, M; Heddle, C; Brown, M; Barclay, N; Halestrap, A (2000)
CD147 is a broadly expressed plasma membrane glycoprotein containing two immunoglobulin-like domains and a single charge-containing transmembrane domain. Here we use co-immunoprecipitation and chemical cross-linking to demonstrate that CD147 specifically interacts with MCT1 and MCT4, two members of the proton-linked monocarboxylate (lactate) transporter family that play a fundamental role in metabolism, but not with MCT2. Studies with a CD2-CD147 chimera implicate the transmembrane and cytoplasmic domains of CD147 in this interaction. In heart cells, CD147 and MCT1 co-localize, concentrating at the t-tubular and intercalated disk regions. In mammalian cell lines, expression is uniform but cross-linking with anti-CD147 antibodies caused MCT1, MCT4 and CD147, but not GLUT1 or MCT2, to redistribute together into 'caps'. In MCT-transfected cells, expressed protein accumulated in a perinuclear compartment, whereas co-transfection with CD147 enabled expression of active MCT1 or MCT4, but not MCT2, in the plasma membrane. We conclude that CD147 facilitates proper expression of MCT1 and MCT4 at the cell surface, where they remain tightly bound to each other. This association may also be important in determining their activity and location.